Investigating the size effect and value premium in the Singapore Exchange - Ang, Qian Lu (2008)
This study sets out to examine if both the size effect and value premium existed in the Singapore Exchange during recent years. It also aims to detect any interaction between size and value so as to allow investors to formulate strategies to maximize gains or minimize losses under the different market conditions.